Become Captain of Your Financial Ship, Unit 2: Trimming the Sails - Josephine Turner (EDIS, 2007)
FCS7222, a 23-page curriculum by Josephine Turner, is Unit 2 in a series on personal financial management. It includes a slide presentation and several fact sheets and worksheets that will help consumers understand the importance of maintaining records, how to begin a record keeping system, and the importance of a savings plan and a risk management plan. Published by the UF Department of Family, Youth and Community Sciences, January 2007.